2007
DOI: 10.1016/j.ajic.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the current status of hospital emergency preparedness for infectious disease outbreaks in Beijing, China

Abstract: Emergency preparedness for infectious disease at hospitals in Beijing was in an early stage of development during this survey. Comprehensive measures should be developed and implemented to enhance their capacity for infectious disease emergency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 5 publications
0
30
2
Order By: Relevance
“…Among all public health emergency response agencies, hospital is the key place to provide medical and psychological services [1-3], and medical staffs are the main force involved in response to public health emergencies. The knowledge, skills, attitudes and behavior of the medical staffs have a direct impact on regional or national public health emergency management [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all public health emergency response agencies, hospital is the key place to provide medical and psychological services [1-3], and medical staffs are the main force involved in response to public health emergencies. The knowledge, skills, attitudes and behavior of the medical staffs have a direct impact on regional or national public health emergency management [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some published reports were only concerning on the portion of knowledge, attitude and behavior, or response capacity. Studies have indicated that the knowledge, attitude and behavior of primary care medical staffs for public health emergency were not satisfactory, the response capacity of primary care medical staffs are relatively low [3,8-12]. Their knowledge and attitude on emergency reflect their level of theoretical knowledge and belief.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors described the infectious disease impact of mass casualty incidents and infection prevention interventions that will be required for an effective disaster response but did not specify the role an IP will play in emergency management. 6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Although it may seem that identifying the infection prevention interventions for a disaster is the same as outlining the role an IP will play in emergency management, they are different. Some interventions that can help prevent and contain infection transmission during a disaster, such as diagnosing infectious diseases rapidly and ordering confirmatory laboratory testing, will not be performed by an IP.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In addition, a periodic review as well as updated emergency plans can increase the emergency response capacity of healthcare institutions against such incidents. [23]…”
Section: Discussionmentioning
confidence: 99%
“…[16] Hospitals will face numerous challenges confronting massive influx of patients suffering from bioterrorism disasters and emerging infectious diseases that may be contagious as well. [817] Numerous international studies have reported similar outcomes regarding the lack of preparedness of hospitals in facing biological disasters, such as weakness in planning and organizing,[51018192021] communication,[71122] surge capacity,[58182123] resources,[482022] training and education,[610192021222324] infrastructure,[525] medical management,[7122225] supervision,[371822] and safety and security. [71624]…”
Section: Introductionmentioning
confidence: 99%